Pattern of Skin Diseases in Patients Visiting Universal College of Medical Sciences-Teaching Hospital (UCMS-TH) from the Three Districts of Terai Region in Nepal - Poudyal, Y; Rajbhandari, SL (Journal of Universal College of Medical Sciences, 2014)
INTRODUCTION: The pattern of skin disease varies from country to country and in various regions within same country due to differences in socioeconomic and geographic factors. This study aimed to determine the pattern of skin disease from the three districts of Terai region in Nepal. MATERIALAND METHODS: This was retrospective study done from the hospital OPD patient's record of Universal college of Medical Sciences & Teaching Hospital (UCMS-TH), from 1st September 2011 to 31st August 2012. Patients from Rupandehi, Nawalparasi and Kapilvastu districts were taken. The diagnosis were entered in 15 categories like Acne, Alopecia Areata, Dermatophytosis, Drug reaction, Eczema, Leprosy, Lichen Planus, Melasma, Psoriasis, Pyoderma, Scabies, sexually transmitted diseses (STI), Urticaria, Viral infection and Vitiligo. Any diagnosis not in these categories, was kept at “Other” category. Monthly trend of disease was also analysed. RESULT: Total number of patients from Rupandehi, Kapilvastu and Nawalparasi districts were 12446 (89.3%), 661 (4.7%), 836 (6%) respectively. Dermatophytosis was the commonest 2003 (16.1%) in Rupandehi district, it was second in number in Nawalparasi and Kapilvastu. Eczema was the commonest in Kapilvastu and Nawalparasi district with 103 (15.6%) and 136 (16.3%) respectively. Eczema was second in number in Rupandehi district. Acne was third in number in Rupandehi and Nawalparasi but vitiligo was third common dermatosis recorded in Kapilvastu district. CONCLUSION: Dermatophytosis and Eczema are the most common dermatologic disorders in Terai region. DOI: http://dx.doi.org/10.3126/jucms.v2i3.11820 Journal of Universal College of Medical Sciences Vol.2(3) 2014: 3-8